PENGARUH PERUBAHAN MODAL KERJA TERHADAP PERUBAHAN PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Noer Sasangko; Silfia Kusumaningtyas (Benefit: Jurnal Manajemen dan Bisnis, 2004)
This research check about influence of change of working capital to change of profitability, whereprofitability proxied entrust in the form of some profitability ratio for example: GPM, OPM, NPM,ROI and ROE. Purpose is performed this research to test influence of change of working capital tochange of profitability from 50 manufacturing business which enlist in BEJ. Result of research indicatethat statistically change of working capital have an effect on to change of profitability, where from ratiosrepresenting proxy of the profitability which really influenced by MK is GPM and OPM. This Matteris proved with t of count obtained for the GPM and OPM were 2,340 (bigger than t of tables) orpursuant to its probability is obtained by p-value for the GPM and OPM were 0,021 (smaller than0,05).